The teacher assignment problem: A special case of the fixed charge transportation problem - Hultberg, T.H.
A basic model of the task of assigning classes to professors, in such a way that the average number of distinct subjects assigned to each professor is minimized, is formulated as a mixed integer program. It turns out that the problem is a special case of the fixed charge transportation problem which in some cases corresponds to finding a basic solution of a transportation problem which is as degenerate as possible. We present an equivalent alternative formulation of the problem which makes it easy to prove that it is NP-hard in the strong sense and an exact branch and bound algorithm for its solution based on this alternative formulation is outlined. Computational experiments with data from a concrete problem, concludes the paper. © 1997 Elsevier Science B.V.